Phase-transfer catalyzed enantioselective α-alkylation of α-acyloxymalonates: construction of chiral α-hydroxy quaternary stereogenic centers. Issue 81 (16th August 2016) - Ha, Min Woo; Choi, Sujee; Kim, Seek; Lee, Jun Young; Lee, Jae Kyun; Lee, Jeeyeon; Hong, Suckchang; Park, Hyeung-geun
Abstract : The enantioselective synthesis of α-acyloxy-α-alkylmalonates was developed as an efficient method for producing chiral α-tertiary alcohols, which are potentially valuable intermediates in the synthesis of natural products and pharmaceuticals. Abstract : The enantioselective synthesis of α-acyloxy-α-alkylmalonates was developed as an efficient method for producing chiral α-tertiary alcohols, which are potentially valuable intermediates in the synthesis of natural products and pharmaceuticals. The efficient enantioselective α-alkylation of diphenylmethyl tert -butyl α-acyloxymalonates was accomplished via phase-transfer catalysis in the presence of ( S, S )-3, 4, 5-trifluorophenyl-NAS bromide to afford the corresponding α-acyloxy-α-alkylmalonates at high chemical (up to 99%) and optical (up to 93% ee) yields, which could be readily converted to versatile chiral intermediates with a chiral α-tertiary alcohol group.